SOME CURRENT PROBLEMS IN ACCOUNTING. - Werntz, William W. (The Accounting Review, 1939)
Abstract This article aims to select from the everyday business of the U.S. Securities and Exchange Commission some frequently recurring situations not as yet controlled by well-defined accounting principles. A very simple example of the problem is the case of a recovery of bad debts and balances in closed banks written off at the date of the reorganization. The registrant had credited these items to earned surplus and profit and loss while our examiners of the statements felt that the credits should have been to capital surplus. A much more important case involving several problems was that of a large investment company holding substantial blocks of stock of several companies. This company restated its capital and wrote down the values of its securities to market, first eliminating earned surplus and charging the balance partly to capital surplus and partly to reserve for investments which had been created from capital surplus. If investments representing control are held by the reorganized company, a question is raised as to the proper treatment of the surplus of the subsidiaries existing at the date of the quasi-reorganization.